Magnetic Resonance Spectroscopy in the Ventral Tegmental Area Distinguishes Responders to Suvorexant Prior to Treatment: A 4-Week Prospective Cohort Study - Izuhara, Muneto; Miura, Shoko; Otsuki, Koji; Nagahama, Michiharu; Hayashida, Maiko; Hashioka, Sadayuki; Asou, Hiroya; Kitagaki, Hajime; Inagaki, Masatoshi (Frontiers in Psychiatry, 2021)
Background: The ventral tegmental area (VTA; a dopaminergic nucleus) plays an important role in the sleep-wake regulation system including orexin system. In addition to neuronal activity, there is increasing evidence for an important role of glial cells (i.e., astrocytes and microglia) in these systems. The present study examined the utility of magnetic resonance spectroscopy (MRS) for detecting neural and/or glial changes in the VTA to distinguish responders from non-responders before treatment with the orexin receptor antagonist suvorexant. Methods: A total of 50 patients were screened and 9 patients were excluded. The remaining 41 patients with insomnia who have or not a psychiatric disease who were expected to receive suvorexant treatment were included in this study. We compared MRS signals in the VTA between responders to suvorexant and non-responders before suvorexant use. Based on previous reports, suvorexant responders were defined as patients who improved ≥3 points on the Pittsburgh Sleep Quality Index after 4 weeks of suvorexant use. MRS data included choline (reflects non-specific cell membrane breakdown, including of glial cells) and N-acetylaspartate (a decrease reflects neuronal degeneration). Results: Among 41 examined patients, 20 patients responded to suvorexant and 21 patients did not. By MRS, the choline/creatine and phosphorylcreatine ratio in the VTA was significantly high in non-responders compared with responders (p = 0.039) before suvorexant treatment. There was no difference in the N-acetylaspartate/creatine and phosphorylcreatine ratio (p = 0.297) between the two groups. Conclusions: Changes in glial viability in the VTA might be used to distinguish responders to suvorexant from non-responders before starting treatment. These findings may help with more appropriate selection of patients for suvorexant treatment in clinical practice. Further, we provide novel possible evidence for a relationship between glial changes in the VTA and the orexin system, which may aid in the development of new hypnotics focusing on the VTA and/or glial cells.